RNA Therapeutics History, Design, Manufacturing, and Applications - Louis, Irina Vlasova-St (IntechOpen, 2023)
RNA therapies evolved as economical and widely applicable individualized treatment solutions. Novel RNA-based therapeutic vaccines (e.g., against SARS-CoV-2 infection) have been proven to be safe and effective, and many of them are approved by the United States Food and Drug Administration (FDA). This book presents distinct classes of RNA therapeutics, ranging from single-stranded antisense oligonucleotides (ASOs) and subclasses of RNA interferences (miRNAs and other RNAi) to in vitro transcribed and in vivo translated mRNAs drugs and RNA vaccines. The book also discusses some of the challenges in RNA drug engineering, delivery, and specificity, as well as highlights the improvement of pharmacological effectiveness in a wide range of diseases.